Assessment of Jordanian High School Students Performances in Computer Subject: Inclusion for Measurements and Evaluation of Learning - Hani, Anwar Bani; Talib, Rohaya (The journal of contemporary issues in business and government, 2021)
Nowadays, every student is able to use technology in school or at home. Computers have become a necessary part in schools for the sake of well teaching style. The low levels of students’ achievement and their computer subject skills weaknesses at the public examinations in Jordan have continued to draw major stakeholders' attention in education. This study examined Jordanian high school students' academic achievement in computer subject, also gender difference in students’ achievement was examined. An ex-post-facto design of descriptive research was adopted for the study. A preform was used to collect data from a sample of (200) students who have been selected using a stratified random sampling procedure from the secondary schools in Jordan/Irbid. The data, which was collected, is the students’ performances in computer subject achievement tests. The data were analyzed using descriptive statistics and an independent-sample t-test. Results showed that the test internal consistency reliability is low; the students performed below average (M=47.02, SD=16.493 (47%).